Effectiveness of Video on Knowledge Gain Regarding Sugarcane Cultivation Practices among the Farmers - Pawar, Rahul; Devendrappa, S; Shree, D A Nithya (Indian Journal of Extension Education, 2023)
Information and communication technology in agriculture provides solutions to agricultural challenges. The study was conducted in Athani taluk of Belagavi District in Karnataka state during 2020-21. ‘Before-After’ without control group experimental design was used to determine the effectiveness of video on knowledge gain regarding sugarcane cultivation practices among farmers. Video developed on “Sugarcane cultivation practices” was the subject matter selected for the study and tested for their effectiveness and acted as treatment for the study. 50 Sugarcane growers were selected for the treatment randomly. The results revealed that highest mean difference 3.72 was observed in case of integrated disease management, followed by integrated pest management (3.62) and weed management (2.38). The farming experience, land holding, achievement motivation, risk orientation, scientific orientation and cosmopoliteness were found to be positive and significantly related with knowledge gain. Therefore, efforts should be taken up to disseminate knowledge about recommended scientific farming practices by using information and communication technology tools especially video to educate farmers and thereby maximizing their benefits. Hence “Video” might be helpful for making the ‘sugarcane grower’ into ‘resource rich farmers’
Keywords: Effectiveness; Knowledge gain; Video and sugarcane cultivation practices